Optic nerve parameters and cognitive function in the Northern Finland Birth Cohort Eye study - Pitkänen, J. (Joel); Veijola, J. (Juha); Barnett, J. (Jennifer); Liinamaa, J. (Johanna); Saarela, V. (Ville) (Informa, 2022)
Abstract Purpose: The optic nerve head (ONH) is a part of the brain that can be easily studied through the transparent medium of the eye. We explored the relationship between the properties of the optic nerve head, the retinal nerve fiber layer (RNFL) and cognitive function. Methods: Participants of the Northern Finland Birth Cohort (NFBC) 1966 underwent an ophthalmic and cognitive assessment after randomization at age 46. The ophthalmological parameters obtained were the disc area and the neuroretinal rim volume of the ONH and the average RNFL thickness. The surrogates used for cognitive function were the paired associates learning test (PAL), level of education, grade point average (GPA) and Humphrey 24–2 perimetric test time (HFA). We did exploratory research between the ophthalmological parameters and the surrogates for cognition and the correlations between the surrogates for cognition. Results: We found that a larger disc area was associated with a higher level of education, faster accomplishment of the HFA (R = −0.065) but a lower GPA (R = −0.084). An increase in neuroretinal rim volume was associated with fewer errors in the PAL test (R = −0.056), higher level of education, higher GPA (R = 0.072) and faster accomplishment of the HFA (R = −0.047). A thicker RNFL was associated with faster accomplishment of the HFA (R = −0.047). Conclusion: We were able to find statistically significant associations between the parameters of the optic nerve head, the RNFL and cognition in the NFBC Eye study. However, the correlations were negligible at best and of limited predictive value.